An econometric investigation of hedging performance of stock index futures in Korea: dynamic versus static hedging. (31st March 2020) - Hasan, Mohammad; Choudhry, Taufiq; Zhang, Yuanyuan
Employing daily data of stock index and stock index futures, this paper empirically investigates the hedging effectiveness of time-varying hedge ratios of emerging futures markets using South Korea as a case. This paper employs eight variants of GARCH models to estimate the hedge ratios along with the conventional methods, and compares the hedging effectiveness of these estimated hedge ratios across model specifications using both within-sample and out-of-sample forecasting performances. In contrast to recent research findings, hedging performance based on a conventional OLS method outperforms the GARCH class models.